Size-structure dynamics of mixed versus pure forest stands - Pretzsch, Hans; Schütze, Gerhard (Forest Systems, 2014)
Mixed species forests are presently on the advance and widely held to provide many ecosystem functions and services better than pure stands. Recent studies well explored species mixing effects at the individual tree or stand level. However, the link between individual and stand level which is represented by the size-structure dynamics of stands, is still hardly understood.Aim of this study: The objective was to analyse how species mixing modifies the size-structure dynamics of mixed compared with pure forest stands. Area of the study: the study was carried out in Southern Germany.Material and Methods: We selected 11long-term experiments comprising 129 plots of un-thinned or just lightly thinned pure and mixed stands of European beech (Fagus sylvatica [ L.]) and analysed their size structure dynamics.Main Results: Based on the Gini coefficient, skewness and kurtosis we show how mixing with Norway spruce (Picea abies [L.] Karst) and sessile oak (Quercus petraea (Matt.) Liebl.) modifies the size-structure dynamics of European beech. The size distribution of beech in mixture mostly lags behind the pure stand, is more size-asymmetric, and the mortality shifts from the smaller diameter classes further to the taller trees than in pure stands.Research highlights: The revealed changes of the size-structure dynamics of beech in mixed versus pure stands result from a modification of both growth partitioning and self-thinning. We draw conclusions of the reduced size growth and size equality of beech in mixed versus pure stands for forest management planning and perspectives for forest research.Keywords: species selection effect; true mixing effect; morphological plasticity; size-distribution; growth partitioning between trees; mode of mortality; European beech (Fagus sylvatica [L.]); Norway spruce (Picea abies [L.] Karst); sessile oak (Quercus petraea (Matt.) Liebl.).